2002
DOI: 10.2175/106143002x139820
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Methyl tert‐Butyl Ether in Water Using Sunlight and a Photocatalyst

Abstract: The use of methyl tert-butyl ether (MTBE) as a gasoline additive has resulted in increasing pollution of groundwater. Most of the conventional treatment technologies are inefficient or costly when the initial concentration of MTBE is low (Ͻ 200 g/L). To find an ecology friendly and inexpensive method for MTBE remediation, we used solar radiation with titanium dioxide (TiO 2 ) as a photocatalyst. For synthetic samples, almost complete degradation (99 ϩ %) of MTBE was observed at the end of 5-hour test run with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The photocatalytic properties were evaluated in the liquid phase decomposition of methyl ter-butyl ether (MTBE) which is a well-known toxic wastewater pollutant. On the best of our knowledge only few researches has been previously reported for the decomposition of MTBE using TiO 2 [16][17][18][19] or Au-supported on titanium dioxide [20] and no one has been reported for the photo-decomposition of MTBE using gold-supported over titania-alumina mixed oxide.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic properties were evaluated in the liquid phase decomposition of methyl ter-butyl ether (MTBE) which is a well-known toxic wastewater pollutant. On the best of our knowledge only few researches has been previously reported for the decomposition of MTBE using TiO 2 [16][17][18][19] or Au-supported on titanium dioxide [20] and no one has been reported for the photo-decomposition of MTBE using gold-supported over titania-alumina mixed oxide.…”
Section: Introductionmentioning
confidence: 99%
“…MTBE is not readily biodegraded (14) due to the presence of its tert-butyl group; however, some aerobic (15) and anaerobic (16) biodegradation has been previously reported. Therefore, there have been a number of recent studies that investigated the use of Advanced Oxidation Technology (AOT) processes for the destruction of MTBE in groundwater (5,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Several studies have been performed considering UV light/TiO 2 slurries (17)(18)(19), Fenton's reagent (20)(21)(22), UV/H2O2 (13,23,24) and O3/H2O2 (25)(26)(27), sonolytic destruction (28,29), and high energy radiation (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there have been a number of recent studies that investigated the use of Advanced Oxidation Technology (AOT) processes for the destruction of MTBE in groundwater (5,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Several studies have been performed considering UV light/TiO 2 slurries (17)(18)(19), Fenton's reagent (20)(21)(22), UV/H2O2 (13,23,24) and O3/H2O2 (25)(26)(27), sonolytic destruction (28,29), and high energy radiation (30)(31)(32)(33)(34). A recent comprehensive comparison of all these techniques (35) with a major emphasis on cost-effectiveness showed that the performance of all of them depended on site-specific conditions such as water flow, observed influent, and required effluent concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The results a study on H2O2 showed that the addition of H2O2 in the photocatalyst system increases the rate of degradation, in order for the efficiency of TiO2 catalyst to increase in the presence of H2O2 [23]. The results of Beretelly et al (2004) showed that the simultaneous presence of H2O2 and TiO2 (UV/TiO2/H2O2) at 254 nm wavelengths resulted in total MTBE degradation in less than 2 h. Therefore, the combination of these processes has a synergistic effect on MTBE degradation [24].…”
Section: Effect Of H2o2mentioning
confidence: 99%